2017
DOI: 10.1016/j.vaccine.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of homologous and heterologous prime-boost immunizations combining MVA-vectored and plant-derived VP2 as a strategy against IBDV

Abstract: Different immunogens such as subunit, DNA or live viral-vectored vaccines against Infectious Bursal Disease virus (IBDV) have been evaluated in the last years. However, the heterologous prime-boost approach using recombinant modified vaccinia Ankara virus (rMVA), which has shown promising results in both mammals and chickens, has not been tried against this pathogen yet. IBD is a highly contagious and immunosuppressive disease of poultry that affects mainly young chicks. It is caused by IBDV, a double-stranded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Mouse monoclonal antibodies have been developed for many years and diverse antibodies have been quickly obtained and applied to virus infection or treatment-related research in animal models[ 20 22 ]. The DNA prime-protein boost immunization approach has been shown to generate high affinity monoclonal antibodies[ 23 , 24 ]. In the present study, we employed this strategy to generate monoclonal antibodies against the SARS-CoV-2 spike protein.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse monoclonal antibodies have been developed for many years and diverse antibodies have been quickly obtained and applied to virus infection or treatment-related research in animal models[ 20 22 ]. The DNA prime-protein boost immunization approach has been shown to generate high affinity monoclonal antibodies[ 23 , 24 ]. In the present study, we employed this strategy to generate monoclonal antibodies against the SARS-CoV-2 spike protein.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the expression of immunogenic hemagglutinin-neuraminidase (HN) protein of NDV in plants, eliciting specific immune responses in chickens and mice ( Hahn et al., 2007 ; Gómez et al., 2009 ; Ma et al., 2020 ; Shahid et al., 2020 ; Nurzijah et al., 2022 ). Similarly, vaccines for infectious bursal disease virus (IBDV) and the poultry parasite Eimeria have been expressed in plants, demonstrating the potential for plant-based vaccine production ( Richetta et al, 2017 ; Lucero et al, 2019 ; Rage et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that VP2 transient expression in N benthamiana represents a viable platform for the production of a safe, economic, and efficacious vaccine against IBD. Our immunogen, consisting of plant protein extract, can both achieve protection against disease when administered im to young chicken and induce uniform long-lasting high titer antibody response in breeder hens in order to provide effective passive immunity to the offspring ( Lucero et al, 2016 , 2019 ; Richetta et al, 2017 ). In the present work, we continued to study the efficacy of the immunogen and demonstrated that it can also elicit a protective immune response when orally administered.…”
Section: Discussionmentioning
confidence: 99%